Pinocembrin alleviates chronic morphine-induced analgesic tolerance and hyperalgesia by inhibiting microglial activation. (3rd October 2022) - Han, Dongfeng; Dong, Weiping; Jiang, Wei
ABSTRACT: Background: Chronic opioid induced analgesic tolerance is a major obstacle in pain management. Microglial activation is involved in morphine tolerance and pinocembrin suppresses microglial activation in several disease models. We aim to investigate whether and how pinocembrin alleviates morphine tolerance. Methods: We induced chronic morphine tolerance in mice by daily morphine injection, with some mice receiving pinocembrin. Analgesic tolerance and hyperalgesia were determined by behavioral assays. The effects of pinocembrin on morphine induced microglial activation, neuroinflammation, and STAT3 activation were determined by Iba1 immunostaining, Il1b and Tnfa mRNA levels and STAT3 phosphorylation. Finally, the effects of STAT3 inhibition on chronic morphine tolerance were assessed. Results: We show that pinocembrin not only suppressed but also reversed preexisting chronic morphine tolerance and hyperalgesia. We found that chronic administration of morphine lead to microglial activation and neuroinflammation, which were suppressed by pinocembrin. Our results reveal a strong connection of STAT3 with morphine tolerance and pinocembrin suppressed morphine-induced STAT3 activation both in vivo and in BV2 cells. Finally, we show that STAT3 inhibition is sufficient to suppress morphine tolerance and hyperalgesia. Conclusion: Our study suggests that pinocembrin effectively prevents and alleviates chronic morphine tolerance through inhibition of STAT3 mediated microglia activation and neuroinflammation.